2019
DOI: 10.1186/s42397-019-0023-4
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids application enhances flowers insecticidal protein content in Bt cotton

Abstract: Background: Low insecticidal protein expression at reproductive organs affect insect resistance in Bt transgenic cotton. In order to enhance flower insecticidal protein expression, the conventional cultivar Sikang1 (S1) and the hybrid cultivar Sikang3 (S3) were used as experimental materials; the applications of selected 5 types of amino acids and 21 types of amino acids were sprayed on the flowers in 2016 and 2017 cotton growing seasons. Results: The flower Bt protein contents increased significantly under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Valine is involved in the biosynthesis of glucosinolates which has a deterring effect on micro-organisms and herbivory [ 37 ]. A previous study showed that by exogenous application of amino acids on flowers of Bt cotton the concentration of Bt proteins could be increased [ 38 ], therefore, proposing that the concentration of Bt proteins could be increased with the upregulation of amino acids. GABA, a non-protein amino acid act as a signaling molecule in plants [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Valine is involved in the biosynthesis of glucosinolates which has a deterring effect on micro-organisms and herbivory [ 37 ]. A previous study showed that by exogenous application of amino acids on flowers of Bt cotton the concentration of Bt proteins could be increased [ 38 ], therefore, proposing that the concentration of Bt proteins could be increased with the upregulation of amino acids. GABA, a non-protein amino acid act as a signaling molecule in plants [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of space, the expression of Bt protein in different organs and different growth stages of the same organ is different, and the overall expression is high in leaves and low in reproductive organs, especially regarding the lowest expression of Bt protein in cotton bolls in the boll period. Moreover, the most serious period of damage to cotton by bollworm is also in the boll stage [11,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%